Application of GUT Matrix in the assessment of pathological manifestations in heritage constructions - Braga, Isaías Carlos; Brandão, Francisco da Silva; Ribeiro, Francisco Roger Carneiro; Diógenes, Aldecira Gadelha (Revista ALCONPAT, 2019)
The present paper presents the application of GUT (Gravity, Urgency, Tendency) Matrix methodology as a tool in the assessment of pathological manifestations in buildings. Three heritage constructions of the historic center of Sobral, Ceará, Brazil were studied through in situ inspections, photographic records and elaboration of the damage map. The GUT Matrix was used as a tool to rank, in each building, priority levels for each damage in order to define their order of treatment. Thus, it was possible to conclude that the applied method can be used as a useful tool to manage the maintenance of buildings through prioritization of the most significant problems and, to contribute directly to the preservation and safety of the built historical heritage.